The evaluation of α-tocopherol concentration instead of α-tocopherol:cholesterol ratio in adult cystic fibrosis patients results in the overestimation of vitamin E deficiency - Sapiejka, Ewa; Krzyżanowska-Jankowska, Patrycja; Walkowiak, Dariusz; Kurek, Szymon; Walkowiak, Jarosław (Journal of Medical Science, 2019)
Introduction. It has been suggested that serum vitamin E concentrations in CF patients may not properly reflect the body resources of vitamin E. Therefore, we aimed to assess vitamin E status in CF adults relating it to reference values for healthy subjects, also taking into account the α‑tocopherol:cholesterol ratio. Material and Methods. The study group was composed of 33 CF patients − 18 (54.5%) females and 15 (45.5%) males − aged from 18 to 47 years. In all CF patients nutritional status and clinical expression of disease − lung function; Pseudomonas aeruginosa colonization; diabetes; cirrhosis; exocrine pancreatic function and vitamin E supplementation were analyzed. Vitamin E (α‑tocopherol) concentration was assessed by high‑performance liquid chromatography (HPLC). Resuls. CF adults have lower vitamin E concentrations (median: 830 µg/dl vs. 1132 µg/dl, p = 0.00174) and higher vitamin E: cholesterol ratio (median: 7.2 mg/g vs. 6.7 mg/g, p < 0.00001) than healthy subjects. The underlying factor that determines this phenomenon is related to low cholesterol levels observed in CF patients. The percentage of low vitamin E concentrations defined in comparison to healthy Polish peers is considerably higher than low vitamin E:cholesterol ratios (39.4% vs. 21.2%, p = 0.0011). Conclusions. The evaluation of α‑tocopherol concentration instead of α‑tocopherol:cholesterol ratio in CF adults results in the overestimation of vitamin E deficiency. Moreover, there is also potentially a large percentage of individuals with excessive vitamin E body resources. However, this aspect demands further studies.